Day care Lansia Aisyiyah: Evaluation of the implementation of the senior school program - Yusron , Ahmad Tajdid Amin; Sari, Ratna (Universitas Sarjanawiyata Tamansiswa, 2025)
The principle of lifelong learning emphasizes the importance of continuing to seek knowledge even into old age. In old age, elderly people often face physical and mental declines, so they need spiritual guidance, self-care, as well as motivation to live the rest of their lives better. The Aisyiyah Branch Leader is present to offer educational and empowerment services for the elderly through the Aisyiyah Elderly Senior School Day Care (DCLA) program. This study aims to examine the education and empowerment provided to the elderly in the DCLA Senior School program, as well as evaluate the effectiveness of the implementation of the program. This study uses a qualitative approach with the Robert Stake responsive model program evaluation method. The location of the research was at the Aisyiyah Elderly Day Care Building (DCLA), involving the chairman, administrators, and participants of the DCLA Senior School program as participants. Data was collected through observation, interviews, and documentation, then analyzed using data reduction techniques, data presentation, and conclusion drawn. The results of the study show that: (1) The purpose of the DCLA Senior School Program is to create healthy, independent, religious, and optimistic elderly people. This program includes main materials, companion materials, and supplementary materials which are held twice a week (Tuesday and Friday) for three months. (2) The antecedent evaluation shows that the program management understands the program objectives well, socialization to participants is carried out effectively, and the available facilities are adequate. Process evaluation (transaction) indicates that the activity is running according to plan, supported by available facilities and competent speakers. Technical problems can be overcome thanks to the cooperation between the management and the enthusiasm of the participants. The outcome evaluation showed that participants benefited significantly in health, spiritual, and social aspects, with changes in attitudes and improved quality of life indicating the success of the program.